Knowledge and Awareness of Fluoride Releasing Dental Materials - V, KARTHIK.; GANESH S, BALAJI; RANI.S, LESLIE (The journal of contemporary issues in business and government, 2020)
Aim: The aim of the study is to create awareness about fluoride releasing dental materials. Introduction: Fluoride was introduced in dentistry over 70 years ago and it is now recognised as the main factor responsible for the dramatic decline in caries prevalence that has been recorded and observed worldwide. The effect of fluoride on demineralisation and remineralisation of incipient caries lesion in enamel and dentin is recognised as the most important mechanism of fluoride action. Materials and method: The sample size of the study was about 300 participants of undergraduate dental students. A set of questionnaires is being created by the use of google form software, the data collection software score and represent the participants answer in pie chart. Result: After getting statistical analysis results. It is clear that people were moderately aware about the fluoride releasing dental materials. Conclusion: The report had concluded about the role of fluoride releasing dental materials and its property of increasing the efficiency of caries control and preventing biofilm formation. From the limitations of the survey, students were moderately aware about the fluoride releasing dental materials.